Genome-wide association analyses identify three new susceptibility loci for primary angle closure glaucoma - Vithana, Eranga N.; Jonas, Jost B. (Nature genetics, 2012)
Primary angle closure glaucoma (PACG) is a major cause of blindness worldwide. We conducted a genome-wide association study including 1,854 PACG cases and 9,608 controls across 5 sample collections in Asia. Replication experiments were conducted in 1,917 PACG cases and 8,943 controls collected from a further 6 sample collections. We report significant associations at three new loci: rs11024102 in PLEKHA7 (per-allele odds ratio (OR) = 1.22; P = 5.33 × 10−12), rs3753841 in COL11A1 (per-allele OR = 1.20; P = 9.22 × 10−10) and rs1015213 located between PCMTD1 and ST18 on chromosome 8q (per-allele OR = 1.50; P = 3.29 × 10−9). Our findings, accumulated across these independent worldwide collections, suggest possible mechanisms explaining the pathogenesis of PACG.